Rat embryonic stem cell-based in vitro testing platform for mammalian embryo toxicology at pre- and post-implantation stages - Quadalti, Corinne; Moretti, Marzia; Ferrazzi, Fabio; Calzà, Laura; Giardino, Luciana; Baldassarro, Vito Antonio (Frontiers in Toxicology, 2025)
IntroductionThe international guidelines outlining the mandatory developmental toxicology studies of new molecules on pre-implantation, post-implantation and organogenesis phases, require a minimum of 60 pregnant female rats for each molecule to be tested. To date, available in vitro methods still have many limitations, resulting in poor translational power.MethodsIn the present study, an innovative in vitro platform is proposed, based on rat embryonic stem cells (RESCs), which is easy to use and suitable for wide-scale screening, mimicking two different developmental stages: i) pre-implant model (undifferentiated pluripotent cells), ii) post-implant model (neuroectodermal lineage differentiation).ResultsThe in vitro platform was validated by testing the toxicity on the pre-implant model of RA itself, as a known teratogen, a member of the environmental pollutant family per- and polyfluoroalkyl substances (PFAS), the perfluorooctanic acid (PFOA), and the endocrine disruptor chemical 2,2‘,6,6‘-tetrabromobisphenol A (TBBPA) as test compound, targeting the thyroid hormone (TH) signal. The post-implant model showed inactivation of the pluripotent markers and activation of the neuroectodermal markers. The preimplant model resulted high responsive and sensitive to the embryotoxic effect of the tested compounds. The TBBPA was selected to test the potential effects of on viability and neuroectodermal differentiation, assessed through colorimetric and cell-based high-content screening methods establishing sub-toxic (20 μM) and toxic (40 μM) doses. A high-throughput gene expression array-based analysis showed a prompt response of the in vitro testing platform to TBBPA treatment. A rescue experiment exploiting a pan-thyroid receptor (pan-TR) inhibitor (1-850) showed that the effects of TBBPA on RESCs was blocked, demonstrating its activity through TRs.DiscussionThe RESCs-based platform allowed reproducible, robust and highly predictable results, thanks to the coupling of RESCs with high-throughput technologies. These results support the possible use of RESCs-based models as a screening platform for developmental toxicity testing to reduce the number of animals currently used for this aim.